World Wide Uncharted Trajectory Outbreak Initiator: Coronavirus [COVID-19] Pathogenesis - Devi, Gajula Chinna (Indian Journal of Pharmaceutical Education and Research, 2021)
The Coronavirus (CoV) belongs to family of Coronaviridae, suborder Coronavirinae and Nidovirales order. CoV causes diseases in human with a just cold, cough and high fever symptoms simultaneously develops in to severe respiratory syndrome and ceases fatal. The source of virus is believed to be “Wet Market” in Wuhan, China. The source of the latest pandemic has not yet been identified exactly but the original host is expected to be bats and mammals, which are host of wide range of Zoonotic viruses. The current trajectory state defines the virus is climbing rest of the world. The article is a descriptive study of CoV types, origin, transmission of virus from bats, mammals and inanimate surfaces to the host cells, life cycle of coronavirus where the Spike protein (S1 and S2) domains fusing with the receptors present on the host cell and other mechanisms. Steps of translation and exocytosis represented diagrammatically to control and mitigate the fatality. Worldwide therapy of the patients, a glance report on drug developments, stage of clinical trials and vaccine research is reported.
Keywords: WHO; Zoonosis; RNA; Receptor; Vaccine